Partnering for sustainable development: case study of a 10-year donor–recipient partnership. Issue 5 (4th July 2019) - Al Sabbagh, Samah; Copeland, Esker
ABSTRACT: Invigorating multi-stakeholder partnerships is seen as a forward-looking approach towards achieving the 2030 Sustainable Development Goals. Managing such collaborations among the many stakeholders can be challenging. Reach Out to Asia/Education Above All Foundation has established promising approaches towards developing transformative partnerships. One such approach employs a partnership framework which includes principles and guidelines for meta-governance. This article discusses this approach by drawing on reflections from a 10-year collaboration. While the scope of the partnership occurred during the MDG era, a reflective study retrospectively considered the relationship between the initiatives undertaken and the global development goals.